2006
DOI: 10.1179/acb.2006.022
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Markers of Sepsis in the Emergency Department

Abstract: Sepsis is defined as the systemic inflammatory response to infection. However, changes in body temperature, heart and respiratory rate and white cell count (the "SIRS" criteria) are not specific enough to identify infected patients in the emergency department. Among many biological parameters, measurement of lactate, central venous oxygen saturation (ScvO2), C-reactive protein (CRP) and procalcitonin (PCT) are of particular interest. Early (within 6h) and goal-directed (ScvO2 > 70%) resuscitation increases sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…Recently, Jong et al have also reported that alcoholics with Klebsiella pneumoniae pneumonia have a rapidly fatal clinical course with a mortality of 100%, even with adequate antibiotic therapy and intensive management [5]. Therefore, it is crucial to identify the risk factors associated with poor outcome and to evaluate the radiological findings as soon as possible, so as to lose no time in initiating appropriate management [6,7].…”
Section: Abstract Klebsiella Pneumoniae Pneumonia Ctmentioning
confidence: 97%
“…Recently, Jong et al have also reported that alcoholics with Klebsiella pneumoniae pneumonia have a rapidly fatal clinical course with a mortality of 100%, even with adequate antibiotic therapy and intensive management [5]. Therefore, it is crucial to identify the risk factors associated with poor outcome and to evaluate the radiological findings as soon as possible, so as to lose no time in initiating appropriate management [6,7].…”
Section: Abstract Klebsiella Pneumoniae Pneumonia Ctmentioning
confidence: 97%
“…14 The use of a definitive WCC as a sign of appendicitis is difficult, as it is well known that the WCC can be either raised or lowered in sepsis. 15 As a result of this variation in WCC in sepsis, using 'raised WCC' as a marker for appendicitis is wrong as patients with a low WCC would cancel out those with a raised WCC in our analysis. This highlights the use of scoring mechanisms for identifying pathology, for example, the Alvarado scoring for appendicitis.…”
mentioning
confidence: 89%
“…Antibiyotik kullanımı, yavaş üreyen mikroorganizma varlığı ya da kültür ortamına konan kanda bakteri bulunmaması gibi nedenlerle yanlış negatif kan kültü-rü sonucuyla karşılaşılması, bakteriyemili yanık olgularında tedaviyi geciktiren önemli bir sorundur. [1][2][3][4] Bu sebeple, hiper-hipotermi, takipne, taşikardi, lökositoz-lökopeni ile kendini gösteren sistemik enflamatuvar cevap sendromu ile sepsis doğrudan ve aniden kendini gösterebilir.…”
Section: Resultsunclassified